2016
DOI: 10.1039/c6tc01505k
|View full text |Cite
|
Sign up to set email alerts
|

Atomically thin binary V–V compound semiconductor: a first-principles study

Abstract: Searching the novel 2D semiconductor is crucial to develop the next-generation lowdimensional electronic device. Using first-principles calculations, we propose a class of unexplored binary V-V compound semiconductor (PN, AsN, SbN, AsP, SbP and SbAs) with monolayer black phosphorene (α) and blue phosphorene (β) structure. Our phonon spectra and room-temperature molecular dynamics (MD) calculations indicate that all compounds are very stable. Moreover, most of compounds are found to present a moderate energy ga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
80
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(96 citation statements)
references
References 42 publications
14
80
0
2
Order By: Relevance
“…In addition to single-element monolayers of group-VA, the recent emergence of their stable binary compounds with tuned electrical and thermal properties has opened up a broad avenue of nanoelectronic and thermoelectric applications [15,16]. A recent theoretical study by Xiao et al [15] revealed that there are 26 stable 2D binary alloys in which their components are from elements of group-VA, including P, As, Bi, and Sb.…”
Section: -Introductionmentioning
confidence: 99%
“…In addition to single-element monolayers of group-VA, the recent emergence of their stable binary compounds with tuned electrical and thermal properties has opened up a broad avenue of nanoelectronic and thermoelectric applications [15,16]. A recent theoretical study by Xiao et al [15] revealed that there are 26 stable 2D binary alloys in which their components are from elements of group-VA, including P, As, Bi, and Sb.…”
Section: -Introductionmentioning
confidence: 99%
“…The desired physical conditions naturally occur in the nonmagnetic compounds known as higher manganese silicides (HMS) with the general formula MnSi γ (γ = 1.731-1.750) [27][28][29]. The HMS share the Nowotny chimney ladder crystal structure with the elongated tetragonal caxis [30][31][32]. It is well known that the process of growing bulk single crystals of HMS is inevitably accompanied by the formation of MnSi precipitates in the shape of lamellae that are oriented perpendicular to the [001] crystallographic direction of the HMS matrix [33][34][35].…”
mentioning
confidence: 99%
“…After the synthesis of very thin films of phosphorus [27] researchers started to seek similar structures in other group-V elements or pnictogens. Recent theoretical studies have predicted that nitrogen [28], phosphorus [29][30][31], arsenic [32][33][34][35], antimony [36][37][38][39], bismuth [40][41][42][43], and compounds of group-V elements [44] can form stable freestanding SL, planar as well as buckled honeycomb (b) structures similar to that of silicene and germanene and also other manifolds, such as SL symmetric (w) and asymmetric (aw) washboard structures, among others. These SL phases are named, respectively, nitrogene, phosphorene, arsenene, antimonene, and bismuthene.…”
Section: Introductionmentioning
confidence: 99%